Tensile and Compressive Behaviour of Early Age Concrete - Barraclough, Andrew (The Concrete Institute of Australia, 2011)
Concrete is relatively weak in tension, but this should not mean the tensile capacity should be ignored, it still has an important role to play when considering early age concrete properties, especially when you are considering lifting at an early concrete strength. The more efficient and sophisticated design techniques become, the better the understanding of material properties needs to be, and in the case of tensile properties the interest is in relation to the cracking behaviour. The adopted test method used in this paper is the less commonly applied direct tension method. This test was not established to redefine a new test regime, but to research the relevance of this test method. This method has been considered a more direct concrete tension representation when considering the capacity of early age concrete. It has overcome the difficulties of centralizing and aligning the specimen, which is inherent in other test methods.Two concrete mixes were used, which represent typical mixes used in the precast industry. These were selected to study the effects of age, compressive strength gain, and the relative tensile strain capacity. The significance of understanding the behaviour of concrete in tension is detailed and the role of tensile properties with fracture mechanisms is explored. It is shown that the relationship between tensile strength is independent of compressive strength gain, mix composition and concrete age. It is also demonstrated, from previously published data that indirect and direct tensile tests reflect different results.